A Study on the Mechanism of Virtual Anchors' Interactivity and Attractiveness Influencing Consumer Trust, Emotional Attitudes, and Purchase Intentions - Li Guang Yu; Wong Chee Hoo; Wei Zhi; Christian Wiradendi Wolor; Usep Suhud (Journal of Applied Data Sciences, 2026)
This study presents a dual-mediation model examining how the interactivity and appeal of virtual streamers affect consumers' purchase intentions. The model is anchored in the "Stimulus-Organism-Response" (S-O-R) framework, seeking to clarify and compare the efficacy of two distinct psychological pathways: cognitive, mediated by perceived trust, and affective, mediated by emotional attitude. A survey of 515 Chinese consumers with prior exposure to virtual streamer e-commerce livestreams was conducted, with the model tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings demonstrate that both interactivity and appeal significantly increase perceived trust and cultivate positive emotional attitudes. Notably, the direct effect of perceived trust on purchase intention is more potent than that of emotional attitude. Intermediary analysis further confirms that both paths are important intermediaries, and the trust intermediary path consistently exerts stronger influence. These results show that in the context of AI-driven virtual anchors, the cognitive-based trust path is more influential than the emotional-based path. By comparing these two paths, this study has improved our theoretical understanding of virtual persuasion and provided a new contribution. In fact, this study puts forward a strategy of "trust first, emotional strengthening" for marketers who use virtual anchors. Future research should investigate the cross-cultural applicability of these findings and the moderating effect of product categories.